Innovative Leadership-Discresive In Improvement Sustainable Village Participation - Suji Suji; Falih Suaedi; Antun Mardiyanta (UNIVERSITAS PAKUAN, 2023)
Although there has been much research on innovative leadership in both private and public organizations, there is still little empirical evidence showing that innovative leadership at the village level can increase community participation in a sustainable manner. The purpose of this study is to describe and analyze comprehensively the characteristics of the village head's innovative leadership in exploring the innovative leadership of the village head in creating sustainable citizen participation in the village of Mojodeso. This research was conducted using a case study approach. Research subjects were selected purposively, data obtained by in-depth interviews, observation and documentation. The findings in this study are the village head's RT Fund Allocation innovation (radical innovation) followed by providing training in making proposals with RT assistance (innovation adoption) when residents compile and carry out the proposed activities while at the same time compiling the reporting so that the capacity of the residents is created to become more empowered and result in optimizing the participation of villagers in a sustainable manner. In addition, the village head's innovative leadership is accompanied by concern and empathy which creates an aspirational and bottom-up nuanced program, equipped with the courage to make discreet decisions and the ability to manage conflict to become functional (Coser, 1956, Ivancevich, Konopaske and Matteson, 2006). Which actually fosters citizen loyalty to always participate actively (Surbakti, 2010) and be involved (Jung Hyun, 2018) in the process of village development. The implication of these findings, in innovative leadership, it is necessary to emphasize discretive innovative capabilities by providing assistance to citizens and capabilities creating and managing conflict becomes functional to increase as well as maintain the active participation of community members in a sustainable manner.